Groundwork of artificial intelligence humanities - Lee, Chankyu (Array, 2020)
The aim of the Artificial Intelligence Humanities is to present humanistic suggestions for our lives and academia regarding how humans will live in a smart city surrounded by artificial intelligence technology. With that purpose in mind, we introduce the groundwork for the Artificial Intelligence Humanities and share our related concerns. As a concept, “Artificial Intelligence Humanities” comprises three elements: “artificial intelligence,” “content of the humanities,” and “methodology of the humanities.” The “content of the humanities,” comprises the derivatives of the traditional humanities, namely, linguistics, literature, history, ethics, sociology, and cultural studies. These five research areas, along with the discipline created through the traditional humanities’ acceptance of the changes brought by the age of intelligence, are derived by reflecting on oneself and the world, and they are applied to the world as it exists today in the age of artificial intelligence and the humanities.